2017
DOI: 10.1007/s12182-016-0144-z
|View full text |Cite
|
Sign up to set email alerts
|

A parametric study of the hydrodynamic roughness produced by a wall coating layer of heavy oil

Abstract: In water-lubricated pipeline transportation of heavy oil and bitumen, a thin oil film typically coats the pipe wall. A detailed study of the hydrodynamic effects of this fouling layer is critical to the design and operation of oil-water pipelines, as it can increase the pipeline pressure loss (and pumping power requirements) by 15 times or more. In this study, a parametric investigation of the hydrodynamic effects caused by the wall coating of viscous oil was conducted. A custom-built rectangular flow cell was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…The most probable reason for the difference is the wall‐fouling layer, which is appropriately neglected in the analysis of CAF but obviously plays an important role in CWAF. The experiments described here demonstrate that μ o has a significant influence on ΔP/L in CWAF, while previous analysis has shown that this influence is exerted through the relationship between μ o and the thickness of the wall‐fouling layer, t c …”
Section: Resultsmentioning
confidence: 48%
See 4 more Smart Citations
“…The most probable reason for the difference is the wall‐fouling layer, which is appropriately neglected in the analysis of CAF but obviously plays an important role in CWAF. The experiments described here demonstrate that μ o has a significant influence on ΔP/L in CWAF, while previous analysis has shown that this influence is exerted through the relationship between μ o and the thickness of the wall‐fouling layer, t c …”
Section: Resultsmentioning
confidence: 48%
“…As mentioned earlier, the dependence of k s and t c on other flow parameters was studied previously by conducting idealized experiments with water flowing over wall coating layers of very viscous oils . The results of those experiments demonstrated a proportional correlation between k s and t c .…”
Section: Determination and Analysis Of Hydrodynamic Roughnessmentioning
confidence: 83%
See 3 more Smart Citations